(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the author analyzed and described the sociocultural and scientific environment of Maverannakhra and India in 16-17 weeks. A takje humanisticheskie and philosophskie vzglyady poeta, Concept love and philosophical-religious concept "Babur-name".